ANALISIS YURIDIS PENGENAAN BEA MASUK ANTI-DUMPING UNI EROPA KEPADA PRODUK STAINLESS STEEL COLD-ROLLED FLAT ASAL INDONESIA: Judicial Analysis of the Imposition of the European Union Anti-Dumping Duties on Cold-Rolled Stainless Steel Flat Products from Indonesia - Tatyana A S A W Notodipuro; Rosdiana Saleh (Faculty of Law, Universitas Trisakti, 2025)
The European Union issued Commission Implementing Regulation (EU) 2021/2012, later amended by Regulation (EU) 2022/433, imposing anti-dumping duties for three years starting November 18, 2021 on cold-rolled flat stainless steel products from Indonesia. This study examines whether the EU’s anti-dumping measures comply with the GATT/WTO framework and assesses their impact. The analysis shows that several elements of the EU’s anti-dumping investigation and the resulting duties are inconsistent with the Anti-Dumping Agreement and GATT 1994. The duties have reduced the competitiveness of Indonesian stainless steel products and led to a significant decline in exports to the EU market. In response to these inconsistencies and their economic consequences, Indonesia brought the dispute to the WTO Dispute Settlement Body (DSB) to seek resolution.